2005
DOI: 10.1016/j.jacc.2005.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Serum Resistin Levels and Insulin Resistance, Inflammation, and Coronary Artery Disease

Abstract: To the Editor:Resistin is an adipocytokine that may link obesity with insulin resistance and diabetes. Steppan et al. (1) reported serum resistin levels to be elevated in obese mice and to be decreased by thiazolidinediones. They also showed that administration of antiresistin antibodies improved insulin sensitivity. However, subsequent studies produced disparate findings regarding the role of resistin in obesity and insulin resistance (2). Although serum resistin levels were reported to be elevated in obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
102
5
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(131 citation statements)
references
References 11 publications
13
102
5
7
Order By: Relevance
“…25,26 In these lines, although resistin mediates diverse biological effects of cytokines, [27][28][29] there was a lack of association between resistin and white blood cell count in our population, a finding that is in contrast with previous reports. 6,28 It should be noted that other more sensitive markers of subclinical inflammation such as C-reactive protein were not estimated in this study, thus the link between hyperresistinemia and inflammation may be missed. Nevertheless, as others have suggested the association of resistin with eGFR is unlikely to be mediated entirely through inflammatory activation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…25,26 In these lines, although resistin mediates diverse biological effects of cytokines, [27][28][29] there was a lack of association between resistin and white blood cell count in our population, a finding that is in contrast with previous reports. 6,28 It should be noted that other more sensitive markers of subclinical inflammation such as C-reactive protein were not estimated in this study, thus the link between hyperresistinemia and inflammation may be missed. Nevertheless, as others have suggested the association of resistin with eGFR is unlikely to be mediated entirely through inflammatory activation.…”
Section: Discussionmentioning
confidence: 93%
“…[1][2][3] Although the pathophysiological role of resistin remains obscure in the setting of human cardiovascular diseases, accumulating evidence support that it promotes endothelial dysfunction and proinflammatory activation, leading to acceleration of subclinical atherosclerosis. [4][5][6][7][8] In these lines, augmented levels of resistin characterize patients with abdominal obesity, 9 type 2 diabetes mellitus 10 as well as essential hypertension 11,12 suggesting involvement of this protein in multiple vascular disease states.…”
Section: Introductionmentioning
confidence: 99%
“…Adipokines and clinical BP phenotypes C Thomopoulos et al ing to acceleration of sub-clinical atherosclerosis, 27 whereas there is in vitro evidence that promotes endothelial cell activation with increased endothelin-1 transcription and increased expression of the adhesion molecule VCAM-1, and enhances tumour necrosis factor-a expression. 6 Furthermore, there is evidence that Adp inhibits the induction of the adhesion molecule VCAM-1 and intercellular adhesion molecule-1 in endothelial cells by Res, suggesting that the balance of the opposing effects of these adipokines at the level of the endothelial cell might be an important determinant of endothelial Table 4 Correlates of log(10)(Adp) and log(10)(Res) A reference category for the dependent variable was considered the normotensive BP phenotype; Adp, adiponectin; Res, resistin; cofactors entered in all models were age, sex, smoking status, waist circumference, 24-h heart rate, difference standing minus sitting diastolic BP, difference standing minus sitting heart rate, low-density lipoprotein cholesterol, plasma glucose, estimated glomerular filtration rate and left ventricle mass index.…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes and macrophages are thus thought to be the main source of circulating resistin in humans. Human resistin is also considered to be a biomarker or mediator of metabolic and inflammatory diseases, with increased resistin levels having been associated with metabolic disorders such as obesity, insulin resistance, type 2 diabetes and atherosclerotic cardiovascular disease [4][5][6][7][8]. Recent prospective studies such as the Framingham Offspring Study and Multi-Ethnic Study of Atherosclerosis (MESA) thus found that the circulating resistin level was independently associated with the incidence of atherosclerosis [9,10].…”
Section: Introductionmentioning
confidence: 99%